Sustainable financial solutions for the adoption of solar powered irrigation pumps in Nepal’s terai - Mukherji, Aditi; Chowdhury, Devjit Roy; Fishman, Ram; Lamichhane, Nabina; Khadgi, Vijay; Bajracharya, Sugat (CGIAR Research Program on Water, Land and Ecosystems, 2017)
Solar powered irrigation pumps (SPIPs) are a proven technology, and can potentially be a game changer in Nepal’s irrigation sector by providing clean irrigation to millions of farmers. However, the relatively high capital cost of SPIPs is the main impediment that prevents large scale adoption of SPIPs. Given this, can we design appropriate financial solutions that will help in the large scale adoption of this clean and efficient technology? We ran a randomized experiment in order to estimate demand for SPIPs under three financial models – ‘grant’; ‘grant-loan’ and ‘grant-pay as you go’ in Saptari district of Nepal. We provided an additional 10% discount to women applicants, provided they owned the land on which SPIPs were to be installed. These models were based on policies of Alternative Energy Promotion Centre (AEPC), and similar schemes available in India and Bangladesh. Village Development Committees (VDCs) were randomly divided into three groups and one financial option was provided to each group of VDCs. This randomized control trial (RCT) helped estimate absolute demand for each of the models. We ran 45-days promotional campaigns to solicit demand from farmers. The main findings from our experiment were: